Inducing role of thymus in the body’s ageing process - V. A. Kozlov (Медицинская иммунология, 2024)
The ageing process should be considered with respect to all homeostatic systems of the body, their importance for the existence of the organism itself and different timing of their switching-on in the process of age-related changes. An attention should be paid to the literature data on age-related changes in the functional activity of immune system, which starts from almost zero at birth, reaches a maximum at the age of about 40-50 years and significantly decreases during the natural ageing process. The vast majority of most socially significant diseases of modern humans are reasonably associated with this last stage of age-related changes in the functional activity of the immune system. So far, there is probably no consensus on whether ageing is a disease, or not a disease, but just a kind of natural wear of the “biological machine”. In any case, one should emphasize that thymic gland is one of the first organs where negative age-related changes are revealed, one of the two central organs of the immune system. Bone marrow is the second central immune organ. Age-related changes in the thymus are not “all or nothing”, “now or never”, they are normally characterized by a gradual decrease of the cell production and changes in their qualitative characteristics, which undoubtedly result into some negative effects upon the indices of immune system activity. There is a need to develop new approaches towards the assessment of functional parameters of the thymus, highlighting the search for therapeutic approaches that would maintain functional activity of the immune system at a high level.